The First Dual ChE/FAAH Inhibitors: New Perspectives for Alzheimer's Disease? - Rampa, Angela (American Chemical Society, 2012)
[Image: see text] The treatment of Alzheimer's disease (AD) still remains an area of significant unmet need, with drugs that only target the symptoms of the disease. Therefore, there is considerable need for disease-modifying therapies. The complex etiology of AD prompts scientists to develop multitarget strategies to combat causes and symptoms. To this aim, we designed, synthesized, and tested four new carbamates as dual cholinesterase-FAAH inhibitors. The dual activity of these compounds could lead to a potentially more effective treatment for the counteraction of AD progression, because they would allow regulation of both ACh and eCB signaling and improve neuronal transmission and/or counteract neuroinflammation.